Encrypt and Hide Data in True Color Image Classes - Maha Hasso; Shahad Hasso; Ban Maayouf (Al-Rafidain Journal of Computer Sciences and Mathematics, 2013)
In a world that has evolved in which the information and means of transmission within the network of the whole world not to be a convenient way to keep that information to have some privacy or confidentiality had to be hide from some people who may resort to playing with them or use them brings harm to himself and to others and make them exclusive to the needed, and that was the motivation for the selection of research topic, it is aimed primarily to find a new technique to protect data. In this research the application of triple data encryption standard  (3DES)  to encrypt a given text using multiple keys then hide the encrypted text in a true color  image, after selecting their own identity by k-means algorithm for classification and a number of varieties. Data has been hidden as bytes by putting it in the image (depending on the classification) and results showed high accuracy in the hiding did not appear to the human eye is no evidence on the existence of hidden data in the image in each color of the components of the (24 bit), any image that the unit used for the image store 3 bytes of the encrypted text so it is possible using the proposed algorithm to hide the size of any text, without the appearance of any effect on the resulting image. The results showed that the size of the cover image after hiding the encrypted text is the same as it is before the process of hiding, and also found the application to increase or decrease the number of items does not represent a major factor in hiding, but whenever the size of the image is greater (Dimensions), the greater the proportion of hiding. Visual C # language have been used to implement the proposed method.